Third International Congress on Epilepsy, Brain, and Mind: Part 2 - Rektor, Ivan; Schachter, Steven C; Arya, Ravindra; Arzy, Shahar; Braakman, Hilde; Brodie, Martin J; Brugger, Peter; Chang, Bernard S; Guekht, Alla; Hermann, Bruce; Hesdorffer, Dale C; Jones-Gotman, Marilyn; et al. (Epilepsy & behavior, 2015)
Epilepsy is both a disease of the brain and the mind. Here, we present the second of two papers with extended summaries of selected presentations of the Third International Congress on Epilepsy, Brain and Mind (April 3-5, 2014; Brno, Czech Republic). Humanistic, biologic, and therapeutic aspects of epilepsy, particularly those related to the mind, were discussed. The extended summaries provide current overviews of epilepsy, cognitive impairment, and treatment, including brain functional connectivity and functional organization; juvenile myoclonic epilepsy; cognitive problems in newly diagnosed epilepsy; SUDEP including studies on prevention and involvement of the serotoninergic system; aggression and antiepileptic drugs; body, mind, and brain, including pain, orientation, the "self-location", Gourmand syndrome, and obesity; euphoria, obsessions, and compulsions; and circumstantiality and psychiatric comorbidities.
Keywords: Epilepsy; kognitivní poruchy; Anticonvulsants; náhlá smrt; metafyzické vztahy mezi duší a tělem; Internationality; lidé; Myoclonic Epilepsy, Juvenile; kongresy jako téma; internacionalita; antikonvulziva; mozek; myoklonická epilepsie juvenilní; Cognition Disorders; bolest; agrese; epilepsie; Congresses as Topic; Death, Sudden; Brain; Compulsive Behavior; Czech Republic; Mind-Body Relations, Metaphysical; Aggression; Pain; Česká republika; kompulzivní chování; Humans